Addressing DRESS (drug reaction with eosinophilia and systemic symptoms). (December 2015) - McGrath, Catherine M.; Khangura, Karamjit
Abstract : Summary: The syndrome of drug reaction with eosinophilia and systemic symptoms (DRESS) is the manifestation of a severe idiosyncratic drug-induced reaction with variable latency period. DRESS occurs in one in 1000 to one in 10 000 of drug exposures with high rates of long-term sequelae and mortality of around 10%. There are several classes of drugs historically associated with DRESS – aromatic antiepileptics such as carbamazepine and related compounds, nonsteroidal anti-inflammatory drugs, antiretroviral drugs and antibiotics as well as drugs such as sulfasalazine, allopurinol and dapsone. There is growing recognition of the role of genetic predisposition. Implicated alleles can sometimes be used for predrug screening. DRESS can be associated with reactivation of human herpes viruses, which may be important in a prolonged and severe disease course. Prompt recognition of DRESS, withdrawal of the suspect drug under clinical supervision and supportive care are vital.